30 Years of Schengen: Internal blessing, external curse? - Esther Ademmer; Toman Barsbai; Matthias Lücke; Tobias Stöhr (Kiel Institute for the World Economy (IfW), 2015)
We take stock of the Schengen Agreement that celebrated its 30th birthday on June 14th, 2015. We argue that the abolition of internal border controls in most European Union member states is rightly considered a blessing to EU citizens. Internally, the Agreement facilitates social and economic interactions without impeding the security of EU citizens. Externally, the Schengen Agreement has also helped to spread liberal norms and promote EU policies across EU borders, whenever Schengen borders prove permeable enough to allow for legal migration or if the relaxation of Schengen visa requirements is used as a carrot to trigger reforms in EU candidate and neighboring countries. The recent humanitarian crisis at the EU borders reveals that the Schengen system still lacks an appropriate joint asylum policy to counterbalance the loss of internal border controls. This weakness may undermine one of the main achievements of European integration. This Policy Brief revisits the accomplishments of 30 years of Schengen. We first ask how Schengen has affected member states and their citizens and which effects it has exerted on non-Schengen states outside of the EU's borders. We subsequently elaborate on appropriate reforms of a communitarized asylum policy that is needed to safeguard the accomplishments of the Schengen Agreement in the future.
Keywords: 330